2016
DOI: 10.1016/j.physd.2015.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of extreme events created by multiple correlated maxima

Abstract: We consider stochastic processes arising from dynamical systems by evaluating an observable function along the orbits of the system. The novelty is that we will consider observables achieving a global maximum value (possible infinite) at multiple points with special emphasis for the case where these maximal points are correlated or bound by belonging to the same orbit of a certain chosen point. These multiple correlated maxima can be seen as a new mechanism creating clustering. We recall that clustering was in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 28 publications
(33 reference statements)
0
19
0
Order By: Relevance
“…This formula for the finite time cluster size distribution was used first in [16] and explicitly written for the first time in [4]. It appeared subsequently in [5,6]. This formula was derived during the proof of the convergence of REPP, which was based on a blocking type of argument.…”
Section: Clustering Of Rare Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…This formula for the finite time cluster size distribution was used first in [16] and explicitly written for the first time in [4]. It appeared subsequently in [5,6]. This formula was derived during the proof of the convergence of REPP, which was based on a blocking type of argument.…”
Section: Clustering Of Rare Eventsmentioning
confidence: 99%
“…Moreover, for sufficiently regular systems, a full dichotomy exists (see [4, 22]), that is, either ζ is periodic and we have clustering or ζ is non‐periodic and we have the absence of clustering with θ=1 and a standard Poisson process as a limit for the REPP. In [5], the authors introduced a new device to create clustering: instead of considering observables maximised at a single point, they consider multiple maximising points and show that if these points are related by belonging to the same orbit, then a fake periodic behaviour emerges, which is responsible for the appearance of clustering of extreme observations. In this case, the maximal points need not to be periodic but the maximal set that they form, that is, the set of points where the observable attains the global maximum of the observable φ, is periodic in the sense that it recurs to itself after a finite number of iterations.…”
Section: Introductionmentioning
confidence: 99%
“…. , ξ k ∈ X , with k ∈ N, as in [HNT12,AFFR16], we assume that the maximum is achieved on a countable set M = {ξ i } i∈N 0 , which is the closure of a subset of the orbit of some chosen point ζ ∈ X . More precisely, for a certain point ζ ∈ X , we have that M := {f m i (ζ) : i ∈ N}.…”
Section: The Settingmentioning
confidence: 99%
“…Very recently, in [AFFR16], the authors considered the possibility of having a finite number of maximal points of ϕ. Moreover, it was shown that when these maximal points are correlated, in the sense of belonging to the same orbit of some point (not necessarily periodic), then clustering of exceedances is created by what turned out to be a mechanism that emulates some sort of fake periodic effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation